2001
DOI: 10.1136/bjo.85.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Urinary neopterin in idiopathic retinal vasculitis

Abstract: Aims-To determine whether urinary neopterin:creatinine (UNC) ratios relate to disease activity in idiopathic retinal vasculitis (RV). Methods-18 patients with RV were prospectively recruited into a year long longitudinal study. Patients collected first morning urine samples on a weekly basis and on the same day completed a diary which documented their subjective view of RV activity and any concurrent infection. They were examined in clinic on a 6-8 weekly basis and an objective assessment was made of RV diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
7
1
1
Order By: Relevance
“…13 In another study, a strong correlation was detected between serum neopterin and CRP in BD. 31 In our study, while a moderate positive correlation was detected in patients between serum neopterin and ESR, no correlation was found between serum neopterin levels and CRP. Nevertheless, a positive moderate correlation between pathergy positivity and serum CRP levels exists in patient group.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…13 In another study, a strong correlation was detected between serum neopterin and CRP in BD. 31 In our study, while a moderate positive correlation was detected in patients between serum neopterin and ESR, no correlation was found between serum neopterin levels and CRP. Nevertheless, a positive moderate correlation between pathergy positivity and serum CRP levels exists in patient group.…”
Section: Discussioncontrasting
confidence: 47%
“…27,30 Investigators point out that measurement of urine neopterin levels could be more meaningful because urine neopterin levels are at least 500-1000 times higher than serum neopterin levels. 31 In active periods of many diseases with inflammation in their course, as neopterin levels rise in body fluids, it can be considered that cell-mediated immunity primarily causes relapse, or factors causing relapse can affect cell-mediated immunity. It was observed that serum neopterin levels of the patients are higher than the control group, but no significant difference of serum neopterin levels was found between active and inactive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this characteristic, it is believed that neopterin can be used as a biochemical activation indicator that supports the clinical findings in the uveitis cases. In a previous study published by Palmer et al, 12 serum levels of NP were found to be higher in patients with retinal vasculitis. On the other hand, the authors did not find a significant increase in urinary neopterin levels in patients with active idiopathic retinal vasculitis flare-ups.…”
Section: Discussionmentioning
confidence: 88%
“…It has been discussed that the neopterin level shows an increase in the urine and serum when the uveitis cases are clinically active. [10][11][12] In one of these studies, Durukan et al investigated the relationship between urinary neopterin levels and disease activity in patients with different types of uveitis such as Behcet uveitis, non-specific posterior uveitis, and anterior uveitis. In their study, urinary neopterin levels were found to be increased in patients with active uveitis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation